PHYSIO-CHEMICAL EVALUATION AND BIOLOGICAL ACTIVITY OF AJUGA BRACTEOSA WALL. AND VIOLA ODOROTO LINN - Shad, Anwar Ali; Zeeshan, M.; Fazal, Hina; Shah, Hamid Ullah; Ahmed, Shabir; Abeer, Hasem; Abd_Allah, E. F.; Ullah, Riaz; Afridi, Hamid; tariq, Akash; Adnan, Muhammad; Asma, - (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Ajuga bracteosa and Viola odorata are frequently used by the native people of Swat-Pakistan for the curing of fever,malaria, cough, urinary and stomach disorders with slightly different practice of usage like raw powdered, extracts, decoction etc.Methods and Materials: Disc Diffusion Method was used for determination of antimicrobial activities of both plants. Nutrient AgarMedia was used for the culturing and growth of all microbial strains. Vitamin C and minerals contents were determined by standardmethod of AOAC. Na and K were analyzed by using flame photometric technique. Micro minerals i.e. “Ni, Cr, Fe, Cu, Zn, Mn, Ca, Pb,and Mg” were determined by Atomic Absorption Spectrophotometer (AAS). Total Soluble Solid (TSS) was determined by using abberefractometer and pH was determined by using pH meter.Results: The present study demonstrates that both plants exhibited antibacterial activities against P. aeruginos, E. coli, S. typhi, B.subtilis and S. aureus. The examined plants showed zone of inhibition for aqueous fraction (50.90, 45.90 %) against P. aeruginosa; forEtOAc fraction (41.37, 57.62%) against C. Albicans and for hexane fraction (25.86, 40.57%) against K. pneumoniae, respectively. Totalof 14 different minerals (Na, K, P, Ca, Mg, Fe, Zn, Mn, Co, Cr, Ni, Cu, Pb, Cd) were determined and it was also observed that both theexamined plants contained significant level of these analyzed minerals. The subject plants contained highest level of magnesium (295.75,145.85 mg 100-1g) and calcium (212.49, 44.00 mg 100-1g) and potassium (152.6, 437.45 mg 100-1g) while moderate level P, Zn, Na andlower amount of Cd, Ni, Mn and Cu using Atomic Absorption, Flame Photometry and spectrophotometric techniques. V. odorata wasfound to contain a higher amount of vitamin C (64.05±12.37mg 100-1g) as compared to A. bracteosa (45.45 ± 7.29 mg 100-1 g).Conclusion: Findings of this study can persuade researchers for future comprehensive phytochemical study of these plants using state ofart techniques and instruments, which include not only isolation of secondary metabolites from these plants but biological evaluation ofisolated compounds both in vivo and in vitro